A concise public speaking handbook - Steven A. Beebe
Part 1: Introduction. - Speaking in Public. - Improving Your Confidence. - Presenting Your First Speech. - Ethics and Free Speech. - Part 2: Analyzing an Audience - Listening. - Analyzing Your Audience. - Adapting to Your Audience as You Speak-- Part 3: Preparing a Speech. - Developing Your Speech. - Gathering Supporting Material. - Supporting Your Speech. - Part 4: Crafting a Speech. - Organizing Your Speech. - Outlining and Revising Your Speech. - Developing an Introduction. - Developing a Conclusion. - Using Words Well. - Part 5: Delivering a Speech. - Methods of Delivery. - Nonverbal Communication. - Verbal Communication. - Delivering Your Speech. - Selecting Presentation Aids. - Preparing and Using Presentation Aids. - Part 6: Types of Speeches. - Informative Speaking. - Understanding Principles of Persuasive Speaking. - Using Persuasive Strategies. - Speaking on Special Occasions. - Speaking in Small Groups.